The influence of the e-catalogue system on fraud prevention in goods and services procurement in the regional government of Mimika Regency - Maria Suryani Widiastuti; Hasan Basri Umar; Yundhy Hafiziandra (Goodwood Publishing, 2024)
Purpose: This study investigates the influence of communication, teamwork, and work culture on employee performance, with self-efficacy as an intervening variable. This study focuses on the employees of the Riau Islands Provincial Bureau of Procurement of Goods and Services. Research Methodology: A quantitative approach was employed with a sample of 103 employees selected through purposive sampling method. Data were collected via structured questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS 24.0 to test both direct and indirect relationships among variables. Results: The findings revealed that communication, teamwork, and work culture significantly influenced employee performance. Additionally, all three factors positively affected self-efficacy, which in turn mediated their relationship with performance. The mediation analysis confirmed that self-efficacy strengthens the impact of communication, teamwork, and work culture on the performance outcomes. Conclusions: Effective communication, cohesive teamwork, and supportive work culture are critical for enhancing employee performance. Self-efficacy is a vital psychological mechanism that translates organizational dynamics into improved outcomes. Limitations: This study was limited to one regional bureau with a relatively small sample size, which restricts the generalizability of the findings to broader contexts. A cross-sectional design also prevents causal inferences. Contribution: This study enriches the digital governance and procurement literature by emphasizing fraud prevention as a key mediator. It underscores the necessity of combining digital innovations with strong internal controls to achieve transparent and effective procurement.